2006
DOI: 10.1074/jbc.m512009200
|View full text |Cite
|
Sign up to set email alerts
|

Individual Timp Deficiencies Differentially Impact Pro-MMP-2 Activation

Abstract: Membrane-type matrix metalloproteinases (MT-MMPsTIMP-4 associates with MMP-2 and MT1-MMP in a manner similar to TIMP-3, but its deletion had no effect on pro-MMP-2 processing. Thus, TIMP-3 provides an inherent regulation over the kinetics of pro-MMP-2 processing, serving at a level distinct from that of TIMP-2 and TIMP-4.Matrix metalloproteinases (MMPs) 2 are fundamental to biological processes because of their ability to cleave and remodel the extracellular matrix (ECM). MT1-MMP is one of six cell surface mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
92
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 65 publications
11
92
1
1
Order By: Relevance
“…44,[73][74][75][76] Accordingly, we found that TIMP-1 deficiency, but not TIMP-2 deficiency, enhanced airway re-epithelialization implying that the regulation of matrilysin-mediated cell spreading and migration is specific to TIMP-1 and is not a generalized process among different members of the TIMP family. Although TIMP-1 can modulate cell apoptosis, survival, and proliferation through MMP-independent mechanisms, 25,77,78 we conclude that the moderating effect TIMP-1 confers on epithelial regeneration is a consequence of its ability to block MMP activity, specifically that of matrilysin.…”
Section: Discussionmentioning
confidence: 70%
“…44,[73][74][75][76] Accordingly, we found that TIMP-1 deficiency, but not TIMP-2 deficiency, enhanced airway re-epithelialization implying that the regulation of matrilysin-mediated cell spreading and migration is specific to TIMP-1 and is not a generalized process among different members of the TIMP family. Although TIMP-1 can modulate cell apoptosis, survival, and proliferation through MMP-independent mechanisms, 25,77,78 we conclude that the moderating effect TIMP-1 confers on epithelial regeneration is a consequence of its ability to block MMP activity, specifically that of matrilysin.…”
Section: Discussionmentioning
confidence: 70%
“…Furthermore, trypsin-2-processed MMP-2 was obtained by incubating purified pro-MMP-2 with trypsin-2 under cell-free conditions (40). Therefore, autoproteolytic processing of trypsin-2-cleaved MMP-2 is not likely to occur, since cellular molecules, such as TIMP-2 and integrin ␣v␤3, may be required for the maturation of partially processed MMP-2 to its fully active form (10,12,33,47). This may explain the partial activation of trypsin-2-processed MMP-2 seen under cell-free conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of TIMP-2 and integrin ␣v␤3 in the autoproteolytic activation of MMP-2 following MT1-MMPcleavage (10,33,47), these molecules are not likely to be involved in the complete activation of factor Xa-processed MMP-2. Full activation of MMP-2 was not affected in MCF-7 cells that express negligible amounts of TIMP-2 and HEK293F cells transfected with integrin ␣v small interfering RNA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The MMP-2 activation seen at 48 h, which is the period of B16F10 cell extravasation, may be particularly important in facilitating extravasation of these cells across the basement membrane in timp-3 À/À lung. Notably, we have recently reported that timp-3 plays a significant role in the inhibition of pro-MMP-2 activation by comparing mouse embryo Enhanced metastatic dissemination to multiple organs W Cruz-Munoz et al fibroblasts deficient in each of the four timp genes (English et al, 2006). In contrast to timp-3 À/À , timp-1 À/À mice show no difference in their lung colonization when challenged with tumorigenic cells in experimental metastasis assays (Soloway et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies show that timp-3 À/À mouse embryonic fibroblasts have accelerated MT1-MMP-dependent pro-MMP-2 activation (English et al, 2006). We asked whether increased extravasation of B16F10 cells in timp-3 À/À lungs associated with increased MMP-2 activation.…”
Section: Enhanced Metastatic Dissemination To Multiple Organs W Cruz-mentioning
confidence: 97%